2016
DOI: 10.3892/ol.2016.5099
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide exerts pro-apoptotic and cell cycle arrest activity on drug-resistant human lung cancer A549/Taxol cells via modulation of MAPK and PI3K/Akt signaling pathways

Abstract: Abstract. Multidrug resistance (MDR) is a major obstacle in the effective chemotherapeutic treatment of cancers. Triptolide (TPL) is a diterpenoid isolated from Tripterygium wilfordii Hook. f., a traditional Chinese medicine. It was demonstrated in our previous study that TPL exerts anti-MDR cancers on various MDR cell lines (including A549/Taxol, MCF-7/ADR and Bel7402/5-Fu). The present study was designed to investigate its anti-proliferative activity on A549/Taxol cells, and explore the underlying mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Also, our current data contradict previous reports [45] of unobserved apoptosis (despite ~50% cell death) in A549 cells treated for 24 h with 200 nM tripchlorolide, a derivative of TL. Moreover, our findings are in agreement with previous studies that have demonstrated activation of the Akt signaling pathway/apoptosis with similar time/TL dosage treatment of cancer cells [7], including A549 cells [46][47][48][49]. Overall, our study indicated that TL promoted apoptosis in NSCLC cells through Akt pathway signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Also, our current data contradict previous reports [45] of unobserved apoptosis (despite ~50% cell death) in A549 cells treated for 24 h with 200 nM tripchlorolide, a derivative of TL. Moreover, our findings are in agreement with previous studies that have demonstrated activation of the Akt signaling pathway/apoptosis with similar time/TL dosage treatment of cancer cells [7], including A549 cells [46][47][48][49]. Overall, our study indicated that TL promoted apoptosis in NSCLC cells through Akt pathway signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis is one of the major goals of chemopreventive agents which inhibit the overall growth of cancer cells. Caspases are well-defined proteases related to apoptosis (17). Activation of caspase-3 and -9 induces the cleavage of PARP, eventually resulting in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 15 18 Its cytotoxic effect against NSCLC has been demonstrated in vitro and in vivo via the inhibition of nuclear factor (NF)-κB; upregulation of p-p38, p-ERK, p-GSK-3β, Bax, and cleaved caspases-3 and -9; and downregulation of p-JNK, p-Akt, and Bcl-2. 19 Moreover, TL exerts its anti-multidrug resistance (MDR) role on A549/Taxol cell lines by inhibiting the NF-κB signaling pathway and selective modulation of mitogen-activated protein kinase signaling. 20 , 21 However, TL has a poor solubility in water (0.017 mg/mL).…”
Section: Introductionmentioning
confidence: 99%